PENGEMBANGAN ENSIKLOPEDIA IPA BERBASIS INTEGRASI ISLAM SAINS UNTUK MENINGKATKAN MOTIVASI SISWA KELAS IV SD NEGERI 003 ENOK KECAMATAN ENOK - Sri Erdawati (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2018)
The purpose of this study was to produce a valid IPA encyclopedia based on Islamic science integration to increase the motivation of fourth grade students of SDN 003 Enok, Enok District. This research was a research and development (R & D) designed, using the Borg and Gall models. Questionnaires and observation were used to obtaion the data. Questionnaire was used to assess the encyclopedia validity carried out by material experts, linguists, media experts, Islamic integration science experts, and science learning practitioners. In addition, it was also distributed to 32 students to find out their motivation and response to the science encyclopedia based on Islamic integration of science that had been developed. Meanwhile, the observation was used to validate students' motivation before and after using the IPA-based encyclopedia of Islamic integration of science developed. Encyclopedia validation was done by changing the qualitative data into quantitative data, then analyzed its entirety and peraspek, theresults was converted into the product feasibility value. While students' motivation was analyzed by statistical test using SPPS 20, by paired sample t-test. The results of the calculation of the IPA encyclopedia based on Islamic integration of science have been developed, based on the assessment of excellent material experts (SB) with a score of 44 and an ideal percentage level of 91.66%. The assessment of linguists is very good (SB) with a score of 23 and an ideal percentage level of 95.83%. The assessment of media experts is very good (SB) with a score of 21 and an ideal percentage level of 87.5%. Very good science integration Islamic science (SB) assessment with a score of 18 and an ideal percentage rate of 90%. The assessment of practitioners of natural science learning is very good (SB) with a score of 97 and an ideal percentage level of 93.16%. While the students' response to the product developed was very good (SB) with a score of 1496 and an ideal percentage level of 89.90%. The motivation validation is determined based on the results of the paired sample t-test. Based on the results of the test, after using the IPA encyclopedia based on Islamic integration of science obtained t count of 41.462 and t table of 2.039 for motivational results. The results of these calculations show that t count> t table, so it can be concluded that there was a significant increase in student motivation before and after using the IPA encyclopedia based on Islamic integration of science.